Management of bacterial blight of cotton induced by Xanthomonas axonopodis pv malvacearum with the use of neem based formulations - and J.P. VERMA, S.S. HULLOLI, R.P. SINGH (Indian Phytopathology, 2002)
The MIC of the neem (Azadirachta indica) based formulations plantolyte and agricare against X. axonopodis pv. malvacearum was 1Î¼g/ml. This was lower than the MIC of aminoglycosides, streptomycin and kanamycin (2.5Î¼g/ml). When mixed at 0.5Î¼g/ml with antibiotics/fungicides, these neem formulations reduced their MIC and completely inhibited the development of drug resistant mutants, suggesting that they acted not only synergistically with the antibiotics/fungicides but also reduced their hazardous effects. The neem formulations controlled cotyledonary infection alone or in combination with antibiotics at very low doses. It is concluded that neem based formulations could prove useful for management of bacterial blight of cotton.